Social Media and User Performance in Knowledge Sharing - Setiawan Assegaff; Akwan Sunoto; Hendrawan Hendrawan; Xaverius Sika Sika (IAES Indonesia Section, 2018)
The aimed of this study is to investigate the impact of social media utilization on the student's performances for knowledge sharing in teaching and learning progress. A research model on the basis of the Task-Technology Fit Theory and three hypotheses theory was developed for this study. Model and hypotheses then tested and validated using data obtained from a survey of respondents. The survey was conducted on students at a university in Indonesia. Of the 103 questionnaires filled out by members of the university, 75 questionnaires declared valid and used for further analysis. Data were analyzed using Partial Least Square (PLS) PLS Smart software utilizes V2. This study reveals that student performance in sharing knowledge with social media impact by technology characteristic and social media utilization.